Lithium-carbon composite tape and its manufacturing method

The introduction of a metallic lithium intermediate layer and a porous carbon framework in the lithium-carbon composite tape addresses the issues of low tensile strength and poor adhesion, resulting in improved performance and extended cycle life for lithium batteries.

JP2025507478AActive Publication Date: 2025-03-21CHINA ENERGY LITHIUM
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024518940
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-02-10
Filing Date
2023-03-29
Publication Date
2025-03-21
Estimated Expiration
2043-03-29

AI Technical Summary

Technical Problem

Lithium-carbon composite materials face challenges with low tensile strength and poor adhesion to current collector substrates, leading to swelling and separation issues during battery cycle processes, which affect the cycle life of lithium batteries.

Method used

A lithium-carbon composite tape is developed with a metallic lithium intermediate layer between the substrate and the lithium-carbon material layer, enhancing bonding strength and reducing internal resistance, while the porous carbon framework in the composite layer helps suppress volume changes and dendrite formation.

Benefits of technology

The lithium-carbon composite tape exhibits improved tensile strength, enhanced adhesion to substrates, reduced internal resistance, and extended cycle life of lithium batteries, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025507478000001_ABST
    Figure 2025507478000001_ABST
Patent Text Reader

Abstract

The present invention provides a lithium-carbon composite tape and a manufacturing method thereof. The lithium-carbon composite tape includes a substrate, a metallic lithium intermediate layer located on both sides of the substrate, and a lithium-carbon composite layer located outside the intermediate layer, and the mass fraction of carbon in the lithium-carbon composite layer is 5% to 90%. The substrate layer of the lithium-carbon composite tape provides high-strength tensile performance to the lithium-carbon composite tape, and is suitable for large-scale industrialized production. The metallic lithium intermediate layer tightly bonds the substrate layer and the lithium-carbon composite layer, and the problem of swelling during the preparation of the lithium-carbon composite tape can be avoided. The metallic lithium intermediate layer can effectively reduce the internal resistance of the lithium-carbon composite tape, and the lithium in the intermediate layer is active lithium, which contributes to the battery cycle process and can replenish the consumption of metallic lithium in the lithium-carbon layer. The lithium-carbon composite layer includes a carbon skeleton, which provides a spare space for the deposition of metallic lithium, and can not only suppress the volume change during the metallic lithium cycle process, but also effectively reduce the local current density of the electrode and prevent the formation of lithium dendrites.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention belongs to the field of metallic lithium processing, and in particular to a lithium-carbon composite tape and a method for producing the same. [Background technology]

[0002] Metallic lithium, as a negative electrode material that is expected to be widely applied in the future, has always been the focus of research in the field of lithium batteries. However, pure metallic lithium has problems such as a large volume change during cycling and a tendency to form lithium dendrites, which has hindered its industrialization.

[0003] In order to solve the problems existing in pure metallic lithium, other materials have been composited with metallic lithium to obtain composite materials with better performance and meet the demand for high energy density and long cycle life of lithium batteries. Among them, the composite of inexpensive and widely available carbon materials and metallic lithium is the focus of research. Lithium-carbon composite materials have the role of solving the volume change of the electrode during cycling and suppressing the formation of lithium dendrites, but after carbon materials are added to pure metallic lithium, especially after a high content of carbon materials is added, the tensile strength of the lithium-carbon material decreases, making it difficult to process and difficult to attach to the current collector substrate. In order to improve the bonding strength between the lithium-carbon material and the current collector substrate, the composite is generally performed using a roll press device with a high pressure, but this causes swelling and separation of the current collector and the lithium-carbon material, which causes the performance of the lithium-carbon material to rapidly deteriorate during the battery cycling process and further affects the cycle life of the battery.

[0004] In view of the above, there is a need for a lithium-carbon composite tape having high tensile strength and in which the lithium-carbon material is tightly bonded to the substrate. Summary of the Invention

[0005] In response to the above technical problems, the present invention provides a lithium-carbon composite tape having high tensile strength and in which the lithium-carbon material is tightly bonded to the substrate. In particular, a metallic lithium intermediate layer is provided between the substrate layer and the lithium-carbon material layer. The substrate layer provides high tensile performance as a lithium-carbon composite tape, while the in-situ bonded metallic lithium intermediate layer solves the problem that the substrate layer and the lithium-carbon layer are not tightly bonded to each other, which makes it easy for swelling to occur. In addition, the presence of the metallic lithium intermediate layer can effectively reduce the internal resistance of the lithium-carbon composite tape. The lithium in this layer is active lithium, which contributes to the battery cycle process and can replenish the metallic lithium consumed in the lithium-carbon material layer.

[0006] In order to achieve the above object of the invention, according to one aspect of the present invention, A conductive substrate; a metallic lithium intermediate layer located on each side of the substrate; A lithium-carbon composite layer located on the outer side of the metal interlayer. Including, The lithium-carbon composite material includes a porous carbon skeleton and metallic lithium filled in the voids of the porous carbon skeleton, and the mass fraction of carbon in the lithium-carbon composite material layer is 5% to 90%, and preferably 15% to 65%. The lithium-carbon composite tape provided herein is a lithium-carbon composite material having a porous carbon skeleton and metallic lithium filled in the voids of the porous carbon skeleton.

[0007] In some embodiments, the substrate is a metal foil material, an organic polymer film material, an inorganic material film material, or a composite film material of these materials.

[0008] In some embodiments, the metal foil material is a foil material obtained from aluminum, copper, nickel, tin, platinum, gold, silver, iron, lead, titanium, indium, zinc, magnesium, beryllium, tungsten, sodium, antimony, or a combination thereof, such as copper foil, aluminum foil, nickel foil, stainless steel foil, punched copper foil, woven copper mesh, stainless steel mesh, etc.

[0009] In some embodiments, the organic polymer film material is a film material made of a polyolefin, a polyester, or a modified polymer containing one or more amino groups, carboxyl groups, hydroxyl groups, imino groups, halogen elements, sulfonic acid groups, nitrate groups, mercapto groups, phenyl groups, or cyano groups, such as polyethylene film material, polypropylene film material, polyacrylonitrile film material, polyethylene terephthalate film material, and the above film materials with holes.

[0010] In some embodiments, the inorganic material film material includes inorganic carbon materials, metal oxides, metal halides, metal nitrides, metal sulfides, metal salts, or film materials obtained from combinations thereof, such as carbon fiber film materials, graphene film materials, carbon nanotube film materials, buckypaper, etc.

[0011] In some embodiments, the composite film material of these materials is a polyacrylonitrile film material with a copper surface plated, a copper foil with an oxide surface plated, a copper mesh with a silver surface plated, or a stainless steel mesh with a lithium surface plated.

[0012] In some embodiments, the thickness of the substrate is from 1 micron to 20 microns, and the porosity of the substrate is from 0% to 85%, for example, from 15% to 85%.

[0013] In some embodiments, the metallic lithium intermediate layer has a thickness of from 20 nm to 5 microns, preferably from 1 micron to 5 microns.

[0014] In some embodiments, the lithium-carbon layer has a thickness between 1 micron and 200 microns, with a preferred thickness range of 5 microns to 50 microns.

[0015] In some embodiments, the porous carbon skeleton of the lithium-carbon composite material is a mesh-like skeleton having a lithium affinity modified layer formed by entanglement of a composite carbon material, the composite carbon material including a crystalline carbon material and an amorphous carbon coating layer covering a surface of the crystalline carbon material, and the amorphous carbon coating layer constitutes the lithium affinity modified layer.

[0016] In some embodiments, the crystalline carbon material comprises one or more of carbon nanotubes, graphene, pyrogenic carbon fibers, graphite, soft carbon, hard carbon, mesophase carbon microspheres, and carbon black.

[0017] In some embodiments, the amorphous carbon coating layer is a carbonized product of an organic material blended with a crystalline carbon material, the organic material being selected from the group consisting of an organic binder, an organic filler, and a crosslinker.

[0018] In some embodiments, the thickness of the amorphous carbon coating layer is in the range of 10 nm to 600 nm.

[0019] In some embodiments, the amorphous carbon coating layer further comprises nano-metal particles embedded therein or on a surface thereof, the nano-metal particles having a size range of 5 nm to 800 nm.

[0020] In some embodiments, the porous carbon framework in the lithium-carbon composite layer has a linear, spherical, sea urchin-like, porous spherical, spherical-like, or flattened structure.

[0021] According to another aspect of the present invention, there is provided a method for producing the above lithium-carbon composite tape, the method being carried out under the protection of an inert gas and comprising the steps of: First step: A pretreatment step of the substrate, in which the substrate is subjected to at least one of deoiling, pre-oxidation, plasma spraying, ultrasonic cleaning, and high temperature treatment. The second step is a metallic lithium intermediate layer preparation step in which a metallic lithium intermediate layer is prepared on the surface of the substrate by roll pressing, doctor blade coating, pressure coating, physical vapor deposition, or electroplating. The third step is a lithium-carbon composite layer preparation step, in which the lithium-carbon composite material is bonded to the metallic lithium intermediate layer by using doctor blade coating, pressure coating and press compounding methods to obtain a lithium-carbon composite tape.

[0022] In some embodiments, the inert gas includes high purity argon gas, high purity helium gas.

[0023] In some embodiments, the lithium-carbon composite material comprises: Step 1: uniformly mixing an organic binder, a filler, a crosslinking agent and a solvent, the filler including a crystalline carbon material, an organic filler and an optional inorganic filler; A step 2 of pre-drying the mixture obtained in the step 1 by removing the solvent; Step 3 is to heat the material obtained in step 2 at a temperature in the range of 300°C to 1200°C under the protection of an inert gas atmosphere, and obtain a porous carbon skeleton after cooling; step 4 of immersing the porous carbon skeleton obtained in step 3 in molten lithium to obtain a lithium-carbon composite material; The present invention is produced by a method comprising the steps of:

[0024] In some embodiments, the mass ratio of the organic binder, the filler, the crosslinking agent, and the solvent is (4 to 15 parts):(10 to 30 parts):(0.01 to 20 parts):(20 to 400 parts).

[0025] In some embodiments, the mass ratio of the crystalline carbon material in the filler is 15% to 100%.

[0026] In some embodiments, the organic binder is selected from the group consisting of polyvinyl alcohol, polyvinylidene fluoride, polybutene styrene, polystyrene, polycarboxylated cellulose, cyanoacrylate, polyacrylic acid, cyclodextrin, cyclic ether derivatives, polyurethane, methacrylate, epoxy resin, vinyl acetate polymer, polyimide, organofluoropolymer, organosiloxane, polyethylene glycol, polyethylene, polyvinyl chloride, polypropylene, glycerin, ethylparaben and its derivatives, monosaccharide or polysaccharide polymers.

[0027] In some embodiments, the organic filler is selected from the group consisting of plastic particulates (polypropylene, polyethylene terephthalate, polystyrene), benzoic acid, sodium benzoate, sorbic acid, potassium sorbate, calcium propionate, and dehydroacetates.

[0028] In some embodiments, the inorganic filler is selected from the group consisting of metal nanoparticles, metal oxides, metal nitrides, calcium carbonate, hydrous magnesium silicate, mica, hydrated silica, and silica.

[0029] In some embodiments, the crosslinking agent is selected from the group consisting of a polymer in which allyl sucrose or pentaerythritol allyl ether is bonded to acrylic acid, benzoyl peroxide, diethylenetriamine, sodium borate hydrate, cellulose derivatives, and isothiazolinone.

[0030] In some embodiments, the solvent is selected from the group consisting of water, tetrachloroethylene, toluene, turpentine, acetone, methyl acetate, ethyl acetate, pentane, n-hexane, cyclohexane, octane, citralva, ethanol, xylene, toluene, cyclohexanone, isopropanol, ethyl ether, propylene oxide, methylbutanone, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, acetonitrile, pyridine, phenol, and ethylenediamine.

[0031] The lithium-carbon composite tape provided by the present invention has at least one of the following advantages: 1. The substrate layer of the lithium-carbon composite tape provides high strength tensile performance to the lithium-carbon composite tape, which is suitable for large-scale industrial production. 2. The metallic lithium interlayer of the lithium-carbon composite tape tightly bonds the substrate layer and the lithium-carbon layer, which avoids the problem of blistering during the manufacturing process of the lithium-carbon composite tape. 3. The presence of the metallic lithium interlayer can effectively reduce the internal resistance of the lithium-carbon composite tape, and the lithium in the metallic lithium interlayer is active lithium, which contributes to the battery cycling process and can replenish the consumption of metallic lithium in the lithium-carbon layer. 4. The lithium-carbon composite layer in the lithium-carbon composite tape contains a porous carbon skeleton, which provides spare space for the deposition of metallic lithium and can suppress the volume change during the metallic lithium cycling process, while reducing the local current density of the electrode and preventing the formation of lithium dendrites. [Brief description of the drawings]

[0032] [Figure 1] FIG. 1 is a schematic diagram of the structure of one of the lithium-carbon composite tapes according to the present invention. [Diagram 2] FIG. 2 shows the lithium-carbon composite tape produced in Example 1. [Diagram 3] FIG. 3 shows the lithium-carbon composite tape produced in Example 6. [Figure 4] FIG. 4 shows the lithium-carbon composite tape produced in Example 7. [Diagram 5] FIG. 5 shows the lithium-carbon composite tape produced in Example 8. [Figure 6] FIG. 6 shows the lithium-carbon composite tape produced in Example 9. [Figure 7] FIG. 7 shows the lithium-carbon composite tape produced in Comparative Example 2. [Figure 8] FIG. 8 is a cycle graph of the batteries assembled from the materials prepared in Example 1, Comparative Example 2, and Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0033] In order to clarify the objectives, technical solutions and advantages of the present invention, the present invention will be described in more detail with reference to the drawings and examples below. It can be understood that the specific examples described herein are merely for the purpose of interpreting the present invention, and are not intended to limit the present invention. The technical features according to the embodiments of the present invention described below can be combined with each other if there is no mutual contradiction.

[0034] One representative structure of the lithium-carbon composite tape of the present invention includes a substrate 1, metallic lithium intermediate layers 2, 2' bonded to both sides of the substrate 1, and lithium-carbon composite layers 3, 3' attached on the metallic lithium intermediate layers, as shown in FIG. 1. The thicknesses of the metallic lithium intermediate layers 2, 2' on both sides of the substrate 1 may be the same or different, and the method for forming the metallic lithium intermediate layers may be the same or different. Similarly, the lithium-carbon composite layers 3, 3' on both sides may be the same or different. Preferably, the metallic lithium intermediate layer 2 and the metallic lithium intermediate layer 2' are the same, and the lithium-carbon composite layer 3 and the lithium-carbon composite layer 3' are the same. EXAMPLES

[0035] Example 1 Substrate pretreatment A rotary plasma cleaning machine (Shenzhen Dongxin High-Tech Automation Equipment Co., Ltd.) was used to clean the 6-micron-thick copper foil, obtaining a copper foil substrate with no dust on the surface.

[0036] Preparation of metallic lithium interlayer Physical vapor deposition is used to deposit a layer of metallic lithium with a thickness of 4 microns on the surface of the copper foil. During the physical vapor deposition process, the vacuum level in the cavity is kept at 5.0×10 -3 Pa, the cavity temperature was 650°C, and the temperature control precision was ±2°C.

[0037] Preparation of lithium-carbon layer Polyvinyl alcohol (Alted Reagents (Shanghai) Co., Ltd.), polystyrene microspheres (Suzhou Weimai New Materials Co., Ltd.), carbon nanotubes (Shandong University), diethylenetriamine (Shanghai Yantai Industrial Co., Ltd.), isothiazolinone (Alted Reagents (Shanghai) Co., Ltd.), silver nanoparticles and deionized water were used in a mass ratio of 6:9:9:5:5:2:75 and mixed uniformly.

[0038] The prepared mixture was pre-dried at 85°C for 5 hours. The pre-dried material was placed in a crucible and subjected to high-temperature treatment under the protection of an inert gas atmosphere to obtain a carbon skeleton material, which was then treated at a high-temperature treatment temperature of 1000°C for 5 hours. The carbon skeleton material prepared as above was brought into contact with molten metallic lithium, and the metallic lithium was immersed in the carbon material. After cooling, a lithium-carbon block material with a three-dimensional carbon skeleton was obtained. After turning, roll pressing, and cutting, a lithium-carbon composite tape with a thickness of 50 microns was obtained.

[0039] The lithium-carbon composite tape prepared as described above was pressed (at a pressure of 2 MPa) with copper foil having metallic lithium deposited on its surface by roll pressing to obtain a lithium-carbon composite tape with a thickness of 60 microns. As shown in Figure 2, the lithium-carbon composite tape thus prepared had an outer lithium-carbon layer that was tightly attached to the copper foil substrate, and the surface of the lithium-carbon layer was flat and not blistered.

[0040] Example 2 Substrate pretreatment A rolled PET (polyethylene terephthalate) film with a thickness of 6 μm was used as the substrate. First, the rolled PET film was dried in a vacuum oven at 80° C. for 24 hours.

[0041] Fabrication of the metal interlayer Vacuum deposition equipment (vacuum degree 10 -3 A lithium layer was vapor-deposited on both sides of a rolled PET film in a vacuum chamber (pressure 1000 MPa, temperature 500°C) until the lithium layer had a thickness of 4 μm.

[0042] Preparation of lithium-carbon layer The lithium-carbon tape produced in Example 1 was combined with a PET film having metallic lithium vapor-deposited on its surface by roll pressing to obtain a lithium-carbon composite tape having a thickness of 60 microns.

[0043] Example 3 The substrate was changed to a polyacrylonitrile film material with a copper-plated surface, but the rest was the same as in Example 2.

[0044] Example 4 The same procedure was followed as in Example 2, except that tin tetrachloride was added to the polyacrylonitrile film material.

[0045] Example 5 The substrate was changed to a polyacrylonitrile film material with aluminum oxide applied to the surface, but the rest was the same as in Example 2.

[0046] Example 6 As shown in FIG. 3, the substrate was changed to punched copper, but the rest was the same as in Example 1.

[0047] Example 7 As shown in FIG. 4, the substrate was changed to a woven copper mesh, but otherwise the same as in Example 1.

[0048] Example 8 As shown in FIG. 5, the substrate was changed to a stainless steel mesh, but the rest was the same as in Example 1.

[0049] Example 9 As shown in FIG. 6, the substrate was changed to carbon nanotube paper, but the rest was the same as in Example 1.

[0050] Example 10 The substrate was changed to graphene paper, but the rest was the same as in Example 1.

[0051] Comparative Example 1 Polyvinyl alcohol (Alted Reagents (Shanghai) Co., Ltd.), polystyrene microspheres (Suzhou Weimai New Materials Co., Ltd.), carbon nanotubes (Shandong University), diethylenetriamine (Shanghai Yantai Industrial Co., Ltd.), isothiazolinone (Alted Reagents (Shanghai) Co., Ltd.), silver nanoparticles and deionized water were used in a mass ratio of 6:9:9:5:5:2:75 and mixed uniformly.

[0052] The prepared mixture was pre-dried at 85°C for 5 hours. The pre-dried material was placed in a crucible and subjected to high-temperature treatment under the protection of an inert gas atmosphere to obtain a carbon skeleton material, which was then treated at a high-temperature treatment temperature of 1000°C for 5 hours. The carbon skeleton material prepared as above was contacted with molten metallic lithium, and the metallic lithium was immersed in the carbon material. After cooling, a lithium-carbon block material with a three-dimensional carbon skeleton was obtained. After turning, roll pressing, and cutting, a lithium-carbon tape with a thickness of 60 microns was obtained.

[0053] Comparative Example 2 Substrate pretreatment A rotary plasma cleaning machine (Shenzhen Dongxin High-Tech Automation Equipment Co., Ltd.) was used to clean the 6-micron-thick copper foil, obtaining a copper foil substrate with no dust on the surface.

[0054] Preparation of lithium-carbon layer Polyvinyl alcohol (Alted Reagents (Shanghai) Co., Ltd.), polystyrene microspheres (Suzhou Weimai New Materials Co., Ltd.), carbon nanotubes (Shandong University), diethylenetriamine (Shanghai Yantai Industrial Co., Ltd.), isothiazolinone (Alted Reagents (Shanghai) Co., Ltd.), silver nanoparticles and deionized water were used in a mass ratio of 6:9:9:5:5:2:75 and mixed uniformly.

[0055] The prepared mixture was pre-dried at 85°C for 5 hours. The pre-dried material was placed in a crucible and subjected to high-temperature treatment under the protection of an inert gas atmosphere to obtain a carbon skeleton material, which was then treated at a high-temperature treatment temperature of 1000°C for 5 hours. The carbon skeleton material prepared as above was contacted with molten metallic lithium, and the metallic lithium was immersed in the carbon material. After cooling, a lithium-carbon composite block material with a three-dimensional carbon skeleton was obtained. After turning, roll pressing, and cutting, a lithium-carbon composite tape with a thickness of 54 microns was obtained.

[0056] The lithium-carbon composite tape prepared as above was pressed and combined with pretreated copper foil by roll pressing (pressure of 2 MPa) to obtain a lithium-carbon composite tape with a thickness of 60 microns. As shown in Figure 7, the lithium-carbon composite tape produced had blisters on the surface, and the lithium-carbon layer and the substrate were not tightly bonded.

[0057] Comparative Example 3 A 50 micron pure lithium tape was used and pressed (at a pressure of 2 MPa) with a copper foil having metallic lithium deposited on its surface by roll pressing to obtain a lithium-copper composite tape. The other steps were the same as in Example 1.

[0058] Peel force measurement: The tape prepared in each example was used to prepare a measurement sample having a width of 25 mm and a length of 150 mm, and the number of samples per example was 5. TESA7475 adhesive tape (Desa Adhesive Co., Ltd.) was attached to the measurement surface of the measurement sample, and roll pressed with a 2 kg standard roller, and the roll pressing was repeated twice. Double-sided adhesive tape was attached to the non-measurement surface of the sample, and the sample was fixed on a standard stainless steel plate and prepared for measurement. One end of the adhesive tape was peeled off from the stainless steel, the stainless steel plate was clamped in the lower jig, and the other end of the adhesive tape was clamped in the upper jig. The measurement test was performed with the speed of the measurement device set to 30 mm / min and the pulling angle set to 180°. The average value of the data measured by the method of pulling the adhesive tape at 180° was recorded as the measurement result.

[0059] Tensile strength measurement Using the tapes produced in each Example, measurement samples with a width of 25 mm and a length of 150 mm were produced, with five samples per Example. The measurement samples were clamped in a measurement jig, and a measurement test was performed with the measurement device speed set to 50 mm / min and a tensile angle of 180°. The maximum tension value was recorded during the material breakage process, and the average value of the maximum tension values ​​was taken to obtain the tensile strength of the material.

[0060] The peel strength and tensile strength values ​​of each of Examples 1 to 10 and Comparative Examples 1 to 3 are shown in the table below. [Table 1]

[0061] As can be seen from Example 1 and Comparative Example 2 in the above table, after preparing the metallic lithium intermediate layer on the copper foil substrate, the peel strength of the lithium-carbon composite tape increased from 55gf / 25mm to 183gf / 25mm, thus indicating that the intermediate layer can significantly increase the adhesion of the lithium-carbon layer to the copper foil substrate. From the tensile test data of Examples 1, 2, 3, 4 and Comparative Example 1, it can be seen that the tensile strength of the lithium-carbon tape itself is low, being only 45MPa, but after the lithium-carbon tape is roll-pressed onto the copper foil or organic polymer substrate (e.g., polyethylene terephthalate, polyacrylonitrile), the tensile strength of the material is obviously increased, which is suitable for the needs of industrialized production.

[0062] The tapes prepared in Example 1, Comparative Example 2, and Comparative Example 3 were used as the negative electrode and a lithium iron phosphate positive electrode to assemble a button battery, a PP film of model number Celgard2500 was used as the separator, and 1M LiPF6, EC:EMC=3:7 (vol / vol) was used as the electrolyte. Charge and discharge measurements were performed on the assembled button battery, with the measurement voltage range set to 2.2 to 3.8 V and the charge and discharge current set to 0.5 C. The measurement graph is shown in FIG.

[0063] As can be seen from FIG. 8, in Comparative Example 3, the material made of pure metallic lithium rapidly attenuated the discharge capacity of the battery after about 85 cycles, and the battery life ended, whereas the battery assembled with the lithium-carbon material had a significantly extended cycle life. Comparative Example 2 also adopted the lithium-carbon material, but since the lithium-carbon material was directly combined with the substrate, the bonding between the substrate and the lithium-carbon material was not good, and the performance of the lithium-carbon material was attenuated, which may be related to the internal resistance of the material. Since the bonding between the materials was not good, the internal resistance increased, and the attenuation rate of the cycle life of the battery was accelerated. In contrast, the battery assembled with the material of Example 1 had the longest cycle life.

[0064] In the examples of the present invention, the lithium-carbon particles and the preparation method thereof according to the present invention are described in detail by combining specific embodiments, but this is for the purpose of fulfilling legal requirements, and the present invention is not limited to the above-described examples. Those skilled in the art can reproduce the lithium-carbon particles and the preparation method thereof by appropriate operations based on the disclosure and teachings of the specification.

[0065] Based on the disclosure and teachings of the above specification, a person skilled in the art can make appropriate changes and modifications to the above embodiment. Therefore, the present invention is not limited to the specific embodiments shown and described above, and some modifications and changes to the present invention should also be included in the scope of protection of the claims of the present invention. In addition, although some specific terms are used in this specification, these terms are for the convenience of explanation and do not limit the present invention in any way.

Claims

1. A conductive substrate; a metallic lithium intermediate layer located on at least one side of the substrate; a lithium-carbon composite layer disposed outside the metal interlayer; The lithium-carbon composite material includes a porous carbon skeleton and metallic lithium filled in voids of the porous carbon skeleton, The mass fraction of carbon in the lithium-carbon composite layer is 5% to 90%. A lithium-carbon composite tape comprising:

2. 2. The lithium-carbon composite tape according to claim 1, wherein the substrate is a metal foil material, an organic polymer film material, an inorganic material film material, or a composite film material of these materials.

3. the metal foil material is a foil material obtained from aluminum, copper, nickel, tin, platinum, gold, silver, iron, lead, titanium, indium, zinc, magnesium, beryllium, tungsten, sodium, antimony, or a combination thereof; The organic polymer film material is a film material made of polyolefin, polyester, or a modified polymer containing one or more of an amino group, a carboxyl group, a hydroxyl group, an imino group, a halogen element, a sulfonic acid group, a nitric acid group, a mercapto group, a phenyl group, and a cyano group, The inorganic material film material includes a film material obtained from an inorganic carbon material, a metal oxide, a metal halide, a metal nitride, a metal sulfide, a metal salt, or a combination thereof; The composite film material of these materials includes polyacrylonitrile film material with copper plated on the surface, copper foil with oxide plated on the surface, copper net with silver plated on the surface, and stainless steel net with lithium plated on the surface.

3. The lithium-carbon composite tape according to claim 2.

4. The lithium-carbon composite tape according to claim 1, characterized in that the lithium-carbon composite tape satisfies at least one of the following requirements: Requirement (1): The thickness of the substrate is 1 micron to 20 microns, and the porosity of the substrate is 0% to 85%. Requirement (2): The thickness of the metallic lithium intermediate layer is 20 nanometers to 5 microns. Requirement (3): The thickness of the lithium-carbon composite layer is 1 micron to 200 microns.

5. The lithium-carbon composite tape according to claim 1, characterized in that the porous carbon skeleton of the lithium-carbon composite material is a mesh-like skeleton formed by entanglement of composite carbon materials and having a lithium affinity modified layer, the composite carbon material includes a crystalline carbon material and an amorphous carbon coating layer covering a surface of the crystalline carbon material, and the amorphous carbon coating layer constitutes the lithium affinity modified layer.

6. The crystalline carbon material includes one or more of carbon nanotubes, graphene, pyrolytic carbon fibers, graphite, soft carbon, hard carbon, mesophase carbon microspheres, and carbon black; the amorphous carbon coating layer is a carbonization product of an organic material blended with a crystalline carbon material, the organic material being selected from the group consisting of an organic binder, an organic filler, and a cross-linking agent; the thickness of the amorphous carbon coating layer is in the range of 10 nm to 600 nm; Additionally, optionally, The amorphous carbon coating layer further includes nano-metal particles embedded therein or on its surface, the nano-metal particles having a size range of 5 nm to 800 nm.

6. The lithium-carbon composite tape according to claim 5.

7. 2. The lithium-carbon composite tape according to claim 1, wherein the porous carbon skeleton in the lithium-carbon composite material layer has a linear, spherical, sea urchin-like, porous spherical, spherical-like or flat structure.

8. 2. The lithium-carbon composite tape of claim 1, wherein the mass fraction of carbon in the lithium-carbon composite layer is 15% to 65%.

9. A method for producing the lithium-carbon composite tape according to any one of claims 1 to 8, comprising the steps of: The method is carried out under inert gas protection and comprises the steps of: First step: a pretreatment step of the substrate, which comprises at least one of deoiling, pre-oxidation, plasma spraying, ultrasonic cleaning, and high-temperature treatment; The second step is a step of preparing a metallic lithium intermediate layer on the surface of the substrate by a method such as roll pressing, doctor blade coating, pressure coating, physical vapor deposition, electroplating, or thermal evaporation; The third step is a lithium-carbon composite layer preparation step, in which the lithium-carbon composite material is bonded to the metallic lithium intermediate layer by doctor blade coating, pressure coating and press compounding to obtain a lithium-carbon composite tape.

10. The manufacturing method according to claim 9, wherein the inert gas includes argon gas and helium gas.

11. The lithium-carbon composite material is Step 1: uniformly mixing an organic binder, a filler, a crosslinking agent and a solvent, the filler including a crystalline carbon material, an organic filler and an optional inorganic filler; A step 2 of pre-drying the mixture obtained in the step 1 by removing the solvent; Step 3, heating the material obtained in step 2 at a temperature in the range of 300° C. to 1200° C. under the protection of an inert gas atmosphere to obtain a porous carbon skeleton after cooling; Step 4 of immersing the porous carbon skeleton obtained in step 3 in molten lithium to obtain a lithium-carbon composite material; The method comprises the steps of: provided that the mass ratio of the organic binder, the filler, the crosslinking agent, and the solvent is 4 to 15 parts: 10 to 30 parts: 0.01 to 20 parts: 20 to 400 parts; The mass ratio of the crystalline carbon material in the filler is 15% to 100%, the organic binder is selected from the group consisting of polyvinyl alcohol, polyvinylidene fluoride, polybutene styrene, polystyrene, polycarboxylated cellulose, cyanoacrylate, polyacrylic acid, cyclodextrin, cyclic ether derivatives, polyurethane, methacrylate, epoxy resin, vinyl acetate polymer, polyimide, organofluoropolymer, organosiloxane, polyethylene glycol, polyethylene, polyvinyl chloride, polypropylene, glycerin, ethylparaben and its derivatives, monosaccharide or polysaccharide polymers; The organic filler is selected from the group consisting of plastic fine particles, benzoic acid, sodium benzoate, sorbic acid, potassium sorbate, calcium propionate, and dehydroacetate; The inorganic filler is selected from the group consisting of metal nanoparticles, metal oxides, metal nitrides, calcium carbonate, hydrous magnesium silicate, mica, hydrated silica, and silica; the crosslinking agent is selected from the group consisting of a polymer in which allyl sucrose or pentaerythritol allyl ether is bound to acrylic acid, benzoyl peroxide, diethylenetriamine, sodium borate hydrate, a cellulose derivative, and isothiazolinone; the solvent is selected from the group consisting of water, tetrachloroethylene, toluene, turpentine oil, acetone, methyl acetate, ethyl acetate, pentane, n-hexane, cyclohexane, octane, citralva, ethanol, xylene, toluene, cyclohexanone, isopropanol, ethyl ether, propylene oxide, methylbutanone, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, acetonitrile, pyridine, phenol, and ethylenediamine; The method according to claim 9 .

Citation Information

Patent Citations

  • Ultra-thin metal lithium complex, preparation method and application thereof

    CN109873122A

  • Novel lithium-containing composite solid-state negative electrode, preparation method thereof and semi-solid-state lithium-sulfur battery

    CN115132971A